Data from: Invasion facilitates hybridization with introgression in the Rattus rattus species complex - Lack, Justin B.; Greene, Daniel U.; Conroy, Chris John; Hamilton, Meredith J.; Braun, Janet K.; Mares, Michael A.; Van den Bussche, Ronald A. (Zenodo, 2012)
Biological invasions result in novel species interactions, which can have significant evolutionary impacts on both native and invading taxa. One evolutionary concern with invasions is hybridization among lineages that were previously isolated, but make secondary contact in their invaded range(s). Black rats, consisting of several morphologically very similar but genetically distinct taxa that collectively have invaded six continents, are arguably the most successful mammalian invaders on the planet. We used mitochondrial cytochrome b sequences, two nuclear gene sequences (Atp5a1 and DHFR), and nine microsatellite loci to examine the distribution of three invasive black rat lineages (R. tanezumi, R. rattus I, and R. rattus IV) in the U.S. and Asia, and determine the extent of hybridization among these taxa. Our analyses revealed two mitochondrial lineages that have spread to multiple continents, including a previously undiscovered population of R. tanezumi in the southeastern U.S., whereas the third lineage (R. rattus IV) appears to be confined to Southeast Asia. Analyses of nuclear DNA (both sequences and microsatellites) suggested significant hybridization is occurring among R. tanezumi and R. rattus I in the U.S., and also suggest hybridization between R. tanezumi and R. rattus IV in Asia, although further sampling of the latter species pair in Asia is required. Furthermore, microsatellite analyses suggest unidirectional introgression from both R. rattus I and R. rattus IV into R. tanezumi. Within the U.S., introgression appears to be occurring to such a pronounced extent that we were unable to detect any nuclear genetic signal for R. tanezumi, and a similar pattern was detected in Asia. Microsatellites Microsatellite data included in this study, formatted for input into GenAlex